A self-sacrifice template strategy to synthesize Co-LDH/MXene for lithium-ion batteries. Issue 86 (14th October 2021) - Li, Chenyang; Dai, Zhiqiang; Liu, Wei; Kantichaimongkol, Pongsakorn; Yu, Pengfei; Pattananuwat, Prasit; Qin, Jiaqian; Zhang, Xinyu
Abstract : A hybrid Co-LDH/MXene is synthesized through a facile water washing method and applied as a good anode for Li-ion batteries. Abstract : To overcome the limitations of both LDHs and MXenes, we develop a self-sacrifice template strategy using a zeolite imidazolate framework-67 (ZIF-67) to derive Co-LDH anchored on an MXene conductive substrate (Co-LDH/MXene). In this process, ZIF-67 grows on the MXene nanosheets, then spontaneously transforms into Co-LDH/MXene in aqueous solution at room temperature. As the LIB anode, it shows a reversible capacity of 854.9 and 398.0 mAh g −1 at 0.1 and 1 A g −1, respectively. This work proposes a feasible synthesis method for the in situ construction of a Co-LDH/MXene hybrid, which may be suitable for other MXenes.